Efficacy and safety of fecal microbiota transplantation for the treatment of irritable bowel syndrome: an overview of overlapping systematic reviews - Zhang, Di; Tang, Yan; Bai, Xiangyu; Li, Da; Zhou, Mengxue; Yu, Chunmei; Wu, Hua (Frontiers in Pharmacology, 2023)
Aim: Evidence from overlapping systematic reviews (SRs) and meta-analyses (MAs) has yielded conflicting results on the treatment of irritable bowel syndrome (IBS) with fecal microbiota transplantation (FMT). To thoroughly gather, assess, and synthesize evidence on FMT for IBS, we carried out the present study. Methods: A comprehensive search was conducted in Cochrane Library, Web of Science, PubMed, and Embase from inception to May 2023. Tools for assessing the methodological quality, reporting quality, and confidence in outcomes, including A Measurement Tool to Assess Systematic Reviews 2 (AMSTAR-2), Preferred Reporting Items for Systematic Reviews and Meta-analyses (PRISMA), and the Grading of Recommendations Assessment, Development and Evaluation (GRADE).Results: Seven eligible SRs/MAs were finally included in this overview. By AMSTAR-2, the methodological quality of SRs/MAs included five that were very low quality, one that was low quality, and one that was high quality. According to PRISMA, limitations were associated with items 5 (Method: Protocol and Registration), 8 (Method: Search), and 27 (Funding). In GRADE, a total of 19 outcomes were included in the seven reviews, of which 12 outcomes were low quality and seven outcomes were moderate quality. Imprecision due to small sample size was the primary factor leading to evidence downgrading.We conclude that there is insufficient evidence to determine whether FMT has a more beneficial effect on patient with IBS than placebo treatment. Well-designed, larger trails are needed to provide evidence in this field. In addition, selection of donor, route of administration, dosage, and frequency still need to be determined.